Clinical characterization of 3-month-old pigs infected with African swine fever virus from Vietnam - Sang-Ik Oh; Vuong Nghia Bui; Duy Tung Dao; Ngoc Anh Bui; Seung-Won Yi; Eunju Kim; Han Gyu Lee; Eun-Yeong Bok; Wimalasena, S.H.M.P.; Young-Hun Jung; Tai-Young Hur; Hu Suk Lee (Korean Society of Veterinary Service, 2022)
African swine fever (ASF) is a fatal viral disease in pigs, with a short incubation period and causing immediate death. Few studies exist on the Asian epidemic ASF virus (ASFV) challenge in older pigs, including growing and fattening pigs and sows. We aimed to investigate clinical outcomes, pathomorphological lesions, and viral distribution in organs of 3-month-old growing pigs that were inoculated with the ASFV isolated in Vietnam. The clinical outcomes were recorded daily, and the dead or euthanized pigs immediately underwent necropsy. Viral loads were determined in 10 major organs using quantitative polymerase chain reaction. The average incubation period in growing pigs was more delayed (5.2±0.9 dpi) than that in weaned pigs, and the clinical signs were milder in growing pigs than in weaned pigs. The digestive and respiratory clinical signs in growing pigs showed at the end period of life, but these were observed at an early stage of infection in weaned pigs. The pathomorphological features were severe and nonspecific with hemorrhagic lesions in various organs. The viral loads in organs from growing pigs were higher than those from piglets, and the number of viral copies was related to gross lesions in the tonsil and intestine. In the absence of vaccines against ASF, early clinical detection is important for preventing the spread of the virus. Our findings elucidated that the clinical signs and gross lesions in growing pigs differed from those in weaned pigs, which provide valuable information for diagnosis of pigs with suspected ASF infection.